Calving and rifting on the McMurdo Ice Shelf, Antarctica - Banwell, AF; Willis, IC; MacDonald, GJ; Goodsell, B; Mayer, DP; Powell, A; MacAyeal, DR (International Glaciological Society, 2017)
ABSTRACT On 2 March 2016, several small en échelon tabular icebergs calved from the seaward front of the McMurdo Ice Shelf, and a previously inactive rift widened and propagated by ~3 km, ~25% of its previous length, setting the stage for the future calving of a ~14 km 2 iceberg. Within 24 h of these events, all remaining land-fast sea ice that had been stabilizing the ice shelf broke-up. The events were witnessed by time-lapse cameras at nearby Scott Base, and put into context using nearby seismic and automatic weather station data, satellite imagery and subsequent ground observation. Although the exact trigger of calving and rifting cannot be identified definitively, seismic records reveal superimposed sets of both long-period (>10 s) sea swell propagating into McMurdo Sound from storm sources beyond Antarctica, and high-energy, locally-sourced, short-period (<10 s) sea swell, in the 4 days before the fast ice break-up and associated ice-shelf calving and rifting. This suggests that sea swell should be studied further as a proximal cause of ice-shelf calving and rifting; if proven, it suggests that ice-shelf stability is tele-connected with far-field storm conditions at lower latitudes, adding a global dimension to the physics of ice-shelf break-up.